(3GdeMGSHI hGdMGSHGJ GdBdjI (B/s - (3eHGQc, UdGM GdOjf YHO GdefYes; (3GdHGHdj, eMeOs ((3GdEScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2008)
(3jVe echfGJ GdMGSH GdBdj , (BWindows XP (3, HQfGeL GcSd hJWHjbGJg GdMSGHjIs
Keywords: (3GdMGSH GdBdjs; (3GdeMGSHIs; (3GdeMGSHI GdBdjIs